2012
DOI: 10.21608/jssae.2012.54354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N, K and N Application Time on Yield and Uptake of Wheat Plants at North Delta

Abstract: A field experiment was carried out during the two successive water seasons of 2002/2003 and 2003/ 2004. The objective of this works was to study the role of N application at tillering stage and effect of K on wheat (Triticum aestivum L.) yield, uptake of N, P, K and N-recovery. The obtained results could be summarized as follows: Grain and straw yields were highly significantly increased with increasing N level up to 120 kg N/fed. (fed=4200 m 2) of the two studied wheat varieties. The highest mean values were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The optimum rate of N, K and B fertilization is one of the important tools to conserve soil properties and improve its productivity as well as getting the maximum wheat yield. Faizy et al (2012) showed that the grain yield of wheat was increased significantly by increasing N levels and the highest grain yield (2.25 tons fed -1 ) was obtained with 120 kg N/fed. Rashed (2011) and Allam (2005) stated that the highest wheat grain and straw yields were produced by applying 90 kg N/fed.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum rate of N, K and B fertilization is one of the important tools to conserve soil properties and improve its productivity as well as getting the maximum wheat yield. Faizy et al (2012) showed that the grain yield of wheat was increased significantly by increasing N levels and the highest grain yield (2.25 tons fed -1 ) was obtained with 120 kg N/fed. Rashed (2011) and Allam (2005) stated that the highest wheat grain and straw yields were produced by applying 90 kg N/fed.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2001). Therefore, Faizy et al (2012) revealed that increasing the level of nitrogen significantly increased wheat grain yield and the highest yield (2.25 tons /fed) was obtained with 120 kg N fed -1 . Also, the grain and straw yields of wheat were significantly increased with increasing N level up to 90 kgfed -1…”
Section: Introductionmentioning
confidence: 96%